Organizations : behavior, structure, processes - Gibson, James L.; Donnelly Jr., James H.;Ivancevich, John M.;Konopaske, Robert (Boston, Massachusetts : McGraw Hill Education, 2003)
The eleventh edition of organizations has been developed to help you understand that in order to effectively manage organizational behavior, you must first have an understanding theory, research, and practice.
Introduction -- Behavior within organizations : individual -- Behavior within organizations : groups and interpersonal influence -- The structure and design of organizations -- The processes of organizations
Includes bibliographical references and index.
Keywords: ORGANIZATIONAL BEHAVIOR